Komunitas Dota 2 Sebagai Digital Brand Community Di Makassar: Studi Netnografi Tentang Loyalitas Merek, Customer Engagement, Dan Konsumsi Esports - Hery Maulana Arif (PT Maju Malaqbi Makkarana, 2026)
This study aims to analyze the DOTA 2 community in Makassar as a form of digital brand community that facilitates the formation of brand loyalty, customer engagement, and local esports consumption. Using a qualitative method with a netnography approach adapted from the Kozinets framework, this study examines the online and offline interactions of DOTA 2 players in Makassar. Data collection was conducted through daily participatory observation, digital document analysis, and in-depth interviews with six key informants who are active in social media groups, Ditusi Gaming Store Discord servers, and cybercafé networks in Makassar between 2024 and 2026. The results of the analysis show that loyalty to DOTA 2 is constructed collectively through consciousness of kind and oppositional loyalty to mobile games. Interactions within South East Asian servers, which are fraught with toxicity and conflict, paradoxically function as a mechanism to strengthen group boundaries and accelerate knowledge sharing in the form of tacit and explicit tactics. Esports consumption is driven by escapism motives, the search for tactical knowledge, and competitive drama, and is supported by local economic transaction infrastructure such as the Ditusi Gaming Store. Theoretically, this research contributes to consumer culture by explaining how antagonistic consumption can sustain the sustainability of brand communities. The managerial implications suggest that marketers position themselves as cultural stewards rather than the absolute owners of commercial brands.